The Relationship Between Length and Weight of Sardine Fish, Sardinella spp - Manginsela, Fransine B.; Lohoo, Anneke V.; Lasabuda, Ridwan; Rustandi, Yogi (Sam Ratulangi University, 2024)
Fish are vertebrates that live all or part of their lives in water, breathe with gills, are equipped with fins for movement and balance, and are cold-blooded (poikilotherm). Lemuru fish are grouped into fish (poikilotherm). Lemuru fish are grouped in the order Cluipeiformes which is part of small pelagic fish. The research was carried out in January-August 2023 to determine the diversity of total length and weight as well as the relationship between the length and weight of male and female lemuru fish, which was carried out using quantitative descriptive methods. Of the 135 lemuru fish individuals observed, there were 40 male individuals with a total length of between 13,184-15,589 cm and 95 female individuals which were longer between 12,083-16,420 cm, and the weight of male individuals between 17,450 - 43,040 grams and female individuals were 19,630 - 52,470 grams. The length-weight regression equation for females is W = 0.018204 L 2.76026 and for males W = 0.01179 L 2.89363.. Keywords: panjang , small pelagic, growth status. Abstrak Ikan adalah vertebrata yang seluruh atau sebagian hidupnya di air, bernafas dengan insang, dilengkapi sirip untuk pergerakan dan keseimbangannya serta berdarah dingin (poikilotherm). Ikan lemuru dikelompokkan pada adalah ikan (poikilotherm). Ikan lemuru dikelompokkan pada ordo Cluipeiformes yang menjadi bagian ikan pelagis kecil. Penelitian dilaksanakan pada bulan Januari-Agustus 2023 bertujuan menentukan keragaman panjang total dan berat serta hubungan panjang berat ikan lemuru jantan dan betina yang pelaksanaannya menggunakan metode deskriptif kuantitatif. Dari 135 individu ikan lemuru yang diamati ada 40 individu jantan dengan panjang total selang 13,184-15,589 cm dan 95 individu betina yang lebih panjang selang 12,083-16,420 cm, dan berat individu jantan selang 17,450 - 43,040 gram dan selang individu betina 19,630 – 52,470 gram. Persamaan regresi panjang-berat betina adalah W = 0.018204 L 2,76026 dan jantan W = 0.01179 L 2,89363. Kata kunci: panjang, berat, regresi, korelasi, Bitung.